2015
DOI: 10.1016/j.str.2014.11.010
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of CDR H3 Structural Diversity

Abstract: Antibody CDR H3 loops are critical for adaptive immunological functions. Although the other five CDR loops adopt predictable canonical structures, H3 conformations have proven unclassifiable, other than an unusual C-terminal “kink” present in most antibodies. To determine why the majority of H3 loops are kinked and to learn whether non-antibody proteins have loop structures similar to H3, we searched a set of 15,679 high-quality non-antibody structures for regions geometrically similar to the residues immediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 63 publications
7
81
0
Order By: Relevance
“…The H3 loop is first completely remodeled in the context of the antibody framework using the next-generation KIC (NGK) loop modeling protocol 21 . For speed, the H3 loop side chains are each reduced to a single low-resolution pseudo-atom, and to ensure sampling of the C-terminal kink conformation 32 , atomic constraints are applied to the governing score function 33 . For subsequent high-resolution refinement, the all-atom CDR H3 side chains are recovered, all CDR side chains are repacked, and the CDR side chains and backbones are minimized.…”
Section: Introductionmentioning
confidence: 99%
“…The H3 loop is first completely remodeled in the context of the antibody framework using the next-generation KIC (NGK) loop modeling protocol 21 . For speed, the H3 loop side chains are each reduced to a single low-resolution pseudo-atom, and to ensure sampling of the C-terminal kink conformation 32 , atomic constraints are applied to the governing score function 33 . For subsequent high-resolution refinement, the all-atom CDR H3 side chains are recovered, all CDR side chains are repacked, and the CDR side chains and backbones are minimized.…”
Section: Introductionmentioning
confidence: 99%
“…A straight conformation of HCDR3 loop with H-bond ladder like in MR78 is infrequent in antibody structures as the majority of the long HCDR3 loops (with >14 amino acids) adopt non-straight (bent or broad) conformations(Tsuchiya and Mizuguchi, 2016). The position of Gly111 residue is more toward the N terminus of the HCDR3 loop, as is expected for loops with a bulged torso conformation(Weitzner et al, 2015). …”
Section: Resultsmentioning
confidence: 62%
“…The dihedral angle α 101 positions the kink relative to the framework of the antibody and the bond angle τ 101 measures the degree of the kink in the torso region. The study showed that the distribution of τ 101 measured for antibody structures is centered at 39° and the distribution of α 101 is centered at 101° (Weitzner et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Especially the diversity of the CDR3 (complementarity-determining region), which has a huge influence on the antigen binding [9,10], is affected with high frequency by this process, because of its position between the V and J gene segments in the heavy chain and between the V and J gene segments in the light chain. The CDR1 and CDR2 loops are not affected by junctional diversity, because of their position in the V gene segment of the heavy and light chain.…”
Section: Junctional Diversity Of Immunoglobulinsmentioning
confidence: 99%